2014
DOI: 10.4137/nmi.s13668
|View full text |Cite
|
Sign up to set email alerts
|

Intense Exercise Increases Protein Oxidation in Spleen and Liver of Mice

Abstract: Studies have indicated that sports anemia is mainly associated with intravascular hemolysis induced by exercise. We hypothesized that such exercise-induced hemolysis leads to oxidative damage due to an increase in free iron caused by hematocyte destruction. Thirty-one male ICR mice were randomly divided into 3 groups: a rested control group, an intense-exercise group, and a group rested for 24 hours after intense exercise. The serum haptoglobin level of the intense-exercise group decreased compared with that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
1
6
0
3
Order By: Relevance
“…22 Many recent studies have examined exercise and the spleen, but most have focused on high-intensity exercise. 23 We did not observe inflammation and tissue necrosis in either group (i.e., the control or low-intensity exercise group), according to the results of hematoxylin-eosin staining. These results indicate that low-intensity exercise does not directly affect the shape of the spleen.…”
Section: Discussionmentioning
confidence: 64%
“…22 Many recent studies have examined exercise and the spleen, but most have focused on high-intensity exercise. 23 We did not observe inflammation and tissue necrosis in either group (i.e., the control or low-intensity exercise group), according to the results of hematoxylin-eosin staining. These results indicate that low-intensity exercise does not directly affect the shape of the spleen.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies [ 24 , 25 ] revealed that structural alterations of erythrocyte membranes, resulting from enhanced generation of free radicals in response to exhaustive or long-term physical exercise, may lead to severe post-exercise hemolysis, which results in an increase in the plasma level of free iron. Under physiological conditions, the iron of heme proteins (hemoglobin, myoglobin, cytochromes) is protected inside a cell.…”
Section: Discussionmentioning
confidence: 99%
“…Yapılan bazı ça-lışmalarda, ağır sportif egzersizlerin eritrosit yıkımına ve intravasküler hemolize neden olabileceği bildirilmiştir. 19 Bunun nedeninin egzersize bağlı ortaya çıkan eritrosit yıkımından gelişebile-ceği rapor edilmiştir. Egzersize bağlı gelişen anemi, eritrositlerin hareket ile fiziksel yıkımı ayrıca laktik asit, lizolesitin, oksidatif stres gibi kimyasal nedenlerle eritrosit membranının yapısının bozulması sonucu şekillenebilir.…”
Section: Koşma Egzersi̇zi̇unclassified
“…Egzersize bağlı gelişen anemi, eritrositlerin hareket ile fiziksel yıkımı ayrıca laktik asit, lizolesitin, oksidatif stres gibi kimyasal nedenlerle eritrosit membranının yapısının bozulması sonucu şekillenebilir. 19 Farelerde ağır egzersizin haptoglobin düzeyini düşürdüğü rapor edilen bir çalışmada, bunun nedeninin intravasküler hemoliz olduğu söylenmiş; ancak aynı çalışmada eritrosit sayısı, hematokrit değer, hemoglobin düzeyi gibi aneminin başlıca göstergesi olan parametrelerin değişmediği de rapor edilmiştir. 119 erişkin ve düzenli egzersiz yapan insanlardan toplanan kan örneklerinin yapılan AFP analizlerinde, gönüllü deneklerin serum haptoglobin konsantrasyonları-nın egzersiz yapmayanlardan %10 oranında daha düşük olduğu belirlenmiştir.…”
Section: Koşma Egzersi̇zi̇unclassified